Micro-segmental analysis of the entry pathway and distribution of zolpidem in hair from different scalp regions after a single dose - Ji, Jiao-Jiao; Xu, Duoqi; Yan, Hui; Xiang, Ping; Shen, Min (Frontiers in Chemistry, 2023)
Introduction: Hair testing is well established for the assessment of past drug exposure; however, more research is needed to understand drug incorporation mechanisms and drug entry pathways into hair. Method: In this study, a micro-segmental LC–MS/MS method was used to analyze a 0.4 mm segment of hair after a single oral administration of zolpidem. Five single hairs were plucked at 1 day, 3 days, 7 days, and 28 days after administration from the vertex posterior of three subjects, and 5 single hairs were also plucked from the parietal, left temporal, and right temporal regions of the head at 28 days. Results and discussion: Proximal S1 (0–0.4 mm) in hair plucked at 1 day had the highest level of zolpidem at 1.5–2.4 pg/mm; much lower concentrations (< 1 pg/mm) were detected at proximal S2–S8 (0.4–3.2 mm). The drug concentration decreased gradually in S1 for 7 days after drug intake and disappeared by 28 days, suggesting that the drug from the bloodstream initially combined with the hair follicle and then gradually moved to the hair tip as the hair grew. The zolpidem concentration–hair segment profiles exhibited a large peak (root side) and a small peak (tip side) for the four sampling times in all three subjects, indicating that drug incorporation in the hair bulb occurred mainly from the blood but probably also entered the hair through sweat and sebum. Zolpidem was also detected in all hairs from the vertex posterior in all three subjects but was not detected in 1 hair from the parietal region and 2 hairs from the left temporal region. The consistency in drug detection, drug concentration level, and peak position was better in hair from the vertex posterior than from the other three regions, indicating that the vertex posterior is a suitable sampling region for estimating drug intake.